Investigating the Role of Communication in Hotel Human Resource Management - Darukhanawalla, Persis (Auckland University of Technology, 2020)
This thesis examines the role of communication in hotel human resource management and explores the impacts of effective and ineffective communication practices for employees within a hotel setting. The hospitality and tourism industry is one of the world’s largest economies and industries. In New Zealand, the hospitality industry is currently the second-largest export earner, making it a huge economic and employment driver for the country. While the country has benefited from the economic gains the industry brings to it, the industry continues to be battled by poor employment conditions of low pay, long hours and lack of work–life balance. These employment conditions have led to the common characteristic of the industry and its biggest downfall: high turnover rates (Jobin, 2011). Poor human resource management practices have also contributed to this because they are another factor of poor employment conditions. Placing more emphasis on effective human resource management processes will lead to employees feeling more valued and thus willing to perform more efficiently in the workplace (Barron, 2008). Communication studies on the hospitality and hotel industry are fairly underdeveloped within the academic realm. This is concerning considering the abundance of academic research available on communication in business and other industries, and the important role communication plays in these industries. Working in the hospitality and hotel industry requires working with people, be they guests or colleagues. Therefore, communication is a key skill required within this industry for processes to work efficiently. Communication is a transferable skill across all industries; however, its implementation requires consistent work and maintenance for the process to become organic and effective. The aim of this thesis was: To investigate hotel employees’ perceived effectiveness of communication from human resource managers and supervisors. The research aim was explored by answering the following questions: 1. How satisfied are hotel employees with the level and quality of communication received from the human resource department and their managers? 2. To what extent do different forms of communication affect perceived communication effectiveness? 3. What are the perceived challenges of effective communication? 4. How do human resource managers try to respond to these challenges? The thesis consists of a literature review written through the lens of an interpretive paradigm for a qualitative methodology. Two qualitative methods were used to produce data for this research: an online employee survey and semi-structured interviews with five human resource managers. The survey findings presented an overwhelmingly positive result from respondents and found that most respondents were satisfied with communication processes. The interview findings presented a thorough overview on key communication forms and the challenges that come with specific forms of communication. This thesis contributes to the literature because it provides a qualitative employee voice from the data collection phase. This aspect is rarely found in the literature because previous studies on communication use a quantitative perspective and focus only on management employees. In addition, this thesis provides a critical insight into internal communication practices and their implications within a hotel setting from the perspective of human resource managers.
Keywords: Hotel; Internal communication; Communication; Human resource management